Elucidating enzymatic polymerisations: Chain-length selectivity of Candida antarctica lipase B towards various aliphatic diols and dicarboxylic acid diesters. (September 2018) - Pellis, Alessandro; Comerford, James W.; Maneffa, Andrew J.; Sipponen, Mika H.; Clark, James H.; Farmer, Thomas J.
Graphical abstract: Highlights: Diesters and diols chain-length selectivity study. Solventless enzymatic polycondensation reactions. Obtained Mw > 10000 Da, Mn > 7000 Da. Abstract: The sustainable synthesis of polymers is a field with growing interest due to the need of modern society to preserve the environment whilst making used products and food sustainable for the future generations. In this work we investigate the possibility of synthesizing aliphatic polyesters derived from various dicarboxylic acid diesters and diols in a solvent-free reaction system. Candida antarctica lipase B was selected as biocatalyst and its selectivity towards the carbon and ester chain length were elucidated. The selected enzyme was able to synthesize various polyesters combining C4 -C10 diesters and C4 -C8 diols. All combinations led to monomer conversions above 90% in 24 h with the best number average molecular weights (Mn ) being obtained through the combination of dimethyl adipate and 1, 8-octanediol leading to a Mn of 7141 Da. Differential scanning calorimetry analysis shows a clear trend with an increase in melting temperature of the polymers that correlates with both the increase of the Mn or of the polymer's constitutional repeat unit carbon chain length. Thermogravimetric analysis and rheology measurements performed on selected samples also confirm the trend showing a variation of the polymer's degradation temperatures and viscosity profiles.